Comparison of machinability of ceramic insert in room temperature and cryogenic cooling conditions during end milling inconel 718 - Amin, A. K. M. Nurul; Mokhtar, Suhaily; Patwari, Muhammed Anayet Ullah; Hazim, A.; Adlan, Z. (IIUM Press, 2011)
Nickel based super alloy or Inconel 718 is known as heat resistant alloys which they are primarily used in gas turbine, steam turbine component and aircraft engine component construction [1]. Inconel 718 attained several unique combinations of properties like strength at elevated temperature, resistance to chemical degradation and wear resistance [2]. However, their ability to maintain these properties at elevated temperatures severely deters the machinability of the alloy, thus it is generally regard to as difficult to machine alloy [3]. The properties of nickel based alloys that contributes to the difficulties in their machining are summarized as follows: (i) major part of its strength is maintained during machining due to high temperature properties; (ii) work hardening occurs rapidly during machining which an ultimate input to notch wear at the tool nose; (iii) cutting tools suffer from high abrasive wear due to the presence of hard abrasive carbides particles in the material; (iv) chemical reaction occurs at high cutting temperatures when machining with normal cutting tool materials, which leads to a high diffusion wear rate; (v) adhesion of nickel alloys onto the cutting tool frequently occur during machining which causing severe notching on the tool rake face due to consequent pull-out of the tool materials; (vi) production of a tough and continuous chip which is difficult to control during machining thus contributing to the degradation of the cutting tool by seizure and cratering; and (vii) poor thermal conductivity of nickel based alloys frequently generates high temperature at the tool tip as well as high thermal gradients in the cutting tool [4]. Due to deprived machinability factors mentioned above, tool life attained when machining nickel based alloys are severely insufficient [5]. Most of main key parameters such as choice of tool materials, tool geometry, machining method, cutting variables and conditions become the causes to achieve sufficient tool life during machining [6]. Several studies on the machining of nickel based alloys had been performed with the use of different tool materials that will contribute to improve machinability and ensure of longer tool life and better surfaced integrity of machined components. Several studies on the machining of nickel based alloys had been performed with the use of different tool materials that will contribute to improve machinability and ensure of longer tool life and better surfaced integrity of machined components. Ceramic tools are currently being used to machine difficult to cut alloys at high speed and in the machining of high hardness work materials due to their improved fracture toughness, thermal shock resistance and lower expansion coefficient [6,7]. Ceramics have intrinsic characteristics such as high melting point, high hardness, good chemical inertness and high wear resistance, which make them, a promising contender for high- temperature structural and wear resistance components [8]. Though ceramic cutting tool possess many advantages, there are some disadvantages related to their low resistance to mechanical shock or low fracture toughness and their low thermal conductivity [9]. With the advances of ceramics technology, the properties of this cutting tool material have been improved performance for machining operations. Ceramic tools are gaining popularity in the machining nickel based alloys because they can withstand higher cutting temperature compared to carbide tools. From these viewpoints, ceramic tools appear to be most suitable as regards tool materials in machining nickel based alloys. Most problems caused during machining Inconel 718 are due to the heat generation and the subsequent high temperatures associated in the machining process which also requires more energy than that in cutting low strength material [10]. Cryogenic is one of a different approach in machining process which the temperature at the cutting zone is reduces to a very low range, to be reduces significantly [11]. Cryogenic cooling approach is a new economical approach which is to make focused liquid nitrogen injected to the chip-tool interface at the point of the highest temperature and the flank at the cutting edge of the tool, in order to improve the tool life [12]. Some works have been recently been done on cryogenic cooling by liquid nitrogen jet in machining which provides less cutting forces, better surface finish and improved tool life of material machining [13-16]. The cryogenic cooling approach is expected to be very useful to elongate the tool life and improving the machinability of Inconel 718.